2017
DOI: 10.1002/jctb.5207
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐functionality ionic liquid mix for extraction and esterification of fatty acids as a step towards increasing the efficiency of conversion of waste cooking oils to biodiesel

Abstract: BACKGROUND The increasing value of pure vegetable oils has made the use of waste cooking oils an attractive alternative feedstock for biodiesel production but the presence of free fatty acids in the waste significantly reduces efficiency of the conversion. RESULTS A low‐temperature mixed ionic liquid system with dual extraction and catalytic functions for the conversion of waste oils containing high levels of free fatty acids to biodiesel was successfully trialled. The solvent, a totally miscible system of HPy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Miquel et al [22] VOCs have been shown to have good solubility in some ILs, the application of these absorbents for VOCs removal has received little attention. A particular advantage of the use of ILs in absorbent methodologies is that in many applications they have been shown to be easily recycled for multiple reuse in a number of processes [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Miquel et al [22] VOCs have been shown to have good solubility in some ILs, the application of these absorbents for VOCs removal has received little attention. A particular advantage of the use of ILs in absorbent methodologies is that in many applications they have been shown to be easily recycled for multiple reuse in a number of processes [24,25].…”
Section: Introductionmentioning
confidence: 99%